Adapting Deep Learning in Practice: Insights from English Teachers’ Perceptions and Reflections on Professional Development - Katrin Pepita; Rojab Siti Rodliyah (Ma'soem University, 2026)
Professional development (PD) is widely recognized as a key mechanism for improving teacher quality and supporting curriculum reform. However, how teachers from different institutional contexts translate sustained PD into their teaching remains underexplored. This qualitative descriptive study investigated two Indonesian junior high school English teachers, one from a public school and one from a private school, who participated in a three-month blended PD program on deep learning pedagogy. Data were collected through semi-structured interviews and analyzed thematically. The findings show that the sustained, multi-stage PD program enabled both teachers to describe efforts to apply deep learning principles in their teaching through reflection, collaboration, and classroom experimentation. However, their experiences differed according to their institutional conditions, professional experiences, and individual beliefs. While the public-school teacher emphasized contextual and affective adaptation, the private-school teacher focused on systematic planning and collegial collaboration while facing different institutional constraints. These findings suggest that the effectiveness of sustained PD depends not only on program design but also on the institutional conditions in which teachers experience and implement new pedagogical practices. The study highlights the importance of context-sensitive PD that supports teachers in adapting curriculum reforms to their own teaching contexts.